Constitutional Theory and Practice: Connecting Legal Philosophy with Legal Reality - Agung Pratama Putra; Sugianto Sugianto; Mohamad Rana (Fakultas Hukum Dehasen, 2024)
This article explores the relationship between legal theory and constitutional practice, focusing on how the principles of legal philosophy are applied in a constitutional context. The constitution not only serves as the supreme legal framework within a country, but it also reflects its underlying values and philosophies. This article examines how various legal theories, including legal positivism, natural law, and critical legal studies, affect the interpretation and application of the constitution. Through this analysis, this article aims to bridge the understanding between legal theory and the reality of constitutional legal practice.